Selective single-bacteria extraction based on capture and release of microemulsion droplets - Li, Jiyu (2023)
Human host-associated microbial communities in body sites can reflect health status based on the population distribution and specific microbial properties in the heterogeneous community. Bacteria identification at the single-cell level provides a reliable biomarker and pathological information for clinical diagnosis. Nevertheless, biosamples obtained from some body sites cannot offer sufficient sample volume and number of target cells as required by most of the existing single-cell isolation methods such as flow cytometry. Herein we report a novel integrated microfluidic system, which consists of a microemulsion module for single-bacteria encapsulation and a sequential microdroplet capture and release module for selectively extracting only the single-bacteria encapsulated in microdroplets. We optimize the system for a success rate of the single-cell extraction to be > 38%. We further verify applicability of the system with prepared cell mixtures (Methylorubrum extorquens AM1 and Methylomicrobium album BG8) and biosamples collected from human skin, to quantify the population distribution of multiple key species in a heterogeneous microbial community. Results indicate perfect viability of the single-cell extracts and compatibility with downstream analyses such as PCR. Together, this research demonstrates that the reported single-bacteria extraction system can be applied in microbiome and pathology research and clinical diagnosis as a clinical or point-of-care device.